Key to the Most Common Species of Thrips Found in Early-Season Blueberry Fields in Florida and Southern Georgia - H. Alejandro Arevalo; A. B. Fraulo; Oscar E. Liburd (EDIS)
ENY-836, a 5-page identification key by H. A. Arevalo, A. B. Fraulo, and O. E. Liburd, provides a dichotomous key to aid in the identification of these important early-season blueberry pests. It incorporates hand-drawn illustrations for specific morphological features to facilitate recognition. Includes references. Published by the UF Department of Entomology and Nematology, October 2006.